Investigating Indonesian Senior High School Students’ Implementation of Self-Regulated Learning towards the English Subject - Indira Lusianingtyas Siswanto; Concilianus Laos Mbato (Universitas Bengkulu, 2020)
English is considered as a foreign language for Indonesian speakers. It also becomes the first obligatory foreign language to be taught in Indonesian Secondary Schools. However, English is rarely used as the medium of communication in the daily life context. Consequently, learners encounter difficulties in uttering sentences and creating written expressions. Therefore, they need to be self-regulated and strategic to acquire English proficiency. The researchers argued that applying self-regulated learning (SRL) by both students and teachers could enhance students’ language mastery. This paper aimed to investigate whether or not self-regulated learning towards the English subject of Grade X and XI students was implemented in one Senior High School in Yogyakarta, Indonesia. It adopted a mixed method approach by distributing questionnaire to 60 students, and conducting a semi-structured interview to one English teacher. One English teacher was chosen as a convenience sample in this study. Based on the finding, the students depict positive results in responding four strategies represented Self-Regulated Learning, including: 1) Planning, 2) Monitoring, 3) Controlling, and 4) Reflecting. Meanwhile, the researcher classified the findings of the teacher’s interview into four major points. The points were: 1) Modelling, 2) Encouraging, 3) Strategic Teaching Method, 4) Outcome Checking and Feedback. From the findings, it could be concluded that both the students and the teacher implemented some aspects of self-regulated learning; even though the process should be conducted more systematically and consistently. Keywords: English learning strategies, self-regulated learning, autonomous learning, English subject